Poziom sprawnosci specjalnej a osiagniecia sportowe 15-16-letnich skoczków o tyczce - Kochanowicz, K.; Klimczyk, M. (Polish Journal of Sport and Tourism, 2012)
Control of specific performance indicators makes it possible to obtain the necessary information for determining dominant characteristics to program sports training taking into account the stage of advancement of sports and athletic performance prediction. Therefore, the aim of the study was to determine the most relevant specific performance indicators in athletes aged 15-16 years practicing the pole vault. Material and methods. The study involved 10 athletes at the first stage at the age of 15 and at the second at the age of 16 practicing pole vault, in the following clubs S.L. WKS, "Zawisza" Bydgoszcz, "Gwardia" Pila, "Slask" Wroc³aw. The study was conducted under training conditions and athletic competition in 2008-2009. The study utilized the method of pedagogical observation and case study. The research tools used involved evaluation of physical fitness and athletic fitness and sporting achievements, conducted during the competition period. To analyze the research results basic statistical methods were used. Conclusions. Special fitness growth dynamics indicators were determined, and analysis of the correlation of these indicators with the sporting achievement was performed. The highest correlation with the pole vault of 0.92 was recorded in an attempt to "fly" over the bar with rollover backwards while doing a handstand. A similar correlation of results was also shown by the special fitness analysis of three competitors with the best results in pole vault. However, in trials of running speed and muscle strength, each of the tested pole vaulters was characterized by an individual development profile.